SACRED GROVES AND ROYAL HUNTS: ENVIRONMENT & POWER IN MEDIEVAL INDIA - Kumar, Rajeev; Rani, Neelam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the intricate relationship between environment and political power in medieval India, focusing on two key dimensions: sacred groves and royal hunts. Sacred groves, protected for religious or cultural reasons, offer insights into indigenous ecological ethics, while royal hunting practices reflect elite control over nature and territorial authority. Using historical texts, inscriptions, and environmental studies, this paper argues that ecological spaces were not only natural entities but also deeply political and symbolic realms in premodern India.